Assessing the Effectiveness of Oral Health Education: Large Versus Small Groups among Primary School Students in Watesjaya, West Java - Dwiyanti, Stephani; Octavia, Mora; Gracia, Isadora; Oktaria, Indriani; Tantra, Cornelia Tyara; Susanto, Alvira; Djiady, Audie; Santoso, Bryan (Universitas Mathla'ul Anwar Banten, 2025)
Insufficient oral health knowledge contributes to high prevalence of oral disease among primary school students. Large-group lectures are commonly used in community services but may not be the most effective learning method. Studies suggest that small-group settings foster better learning environments. This study examines knowledge changes before and after oral health education (OHE), comparing the effectiveness of large- and small-group settings. Fifty-three students aged 10 to 12 years were divided into two groups: Group A (21 students) received OHE in a large lecture-style setting, while Group B (32 students) received OHE in smaller groups of 4 to 8 students. A pre-test was administered before OHE session, followed by a post-test to assess knowledge improvement. Statistical analysis showed significant pre-test to post-test improvement in both groups (p < 0.001). The gain in test scores for group A (27.62+18.69) was greater than that of group B (17.50+10.47), which was also statistically significant (p=0.028). These findings suggest that OHE effectively improves knowledge, with larger groups showing greater score improvement, potentially due to factors such as group dynamics, the physical environment, or learning aids.